MEMAHAMI HADIS-HADIS MUKHTALIF - Nurul Izza, Nadhira; Ariani, Safrina; Agustina, Restika (AL-ATSAR: Jurnal Ilmu Hadits, 2025)
Conflicting hadiths are those that seemingly contradict one another in meaning or content. This presents a hurdle in hadith scholarship. This research emphasizes the significance of comprehending competing hadiths to uphold the legitimacy of Islamic teachings and avert misunderstandings within the society. This research aims to investigate and elucidate the diverse methodologies employed by scholars in addressing conflicts among hadiths. The employed research method is a library study, utilizing data gathered from literature, hadith texts, and pertinent scholarly papers. The research findings suggest that the criterion for the existence of conflicting hadiths entails the presence of two or more acceptable hadiths that seem to contradict one another. The solution of conflicting hadiths encompasses: 1) Compromise (al-jam’u wa al-tawfiq), 2) An ushul fiqh approach, 3) Correlational understanding, 4) Contextual understanding (considering asbabul wurud), 5) Abrogation (naskh), 6) A Tarjih approach, and 7) A Tawwaqquf fi al-ibadah approach. In conclusion, a profound comprehension of the context, sanad, and matan of hadith is essential for attaining a thorough knowledge of the teachings of Prophet Muhammad (peace be upon him). This research hopes to significantly improve the study of hadith and act as a reference for the community in resolving discrepancies stemming from hadith texts. Keywords: Hadith, Mukhtalif, solution Methods.